Inflammatory cytokines induce specific time‐ and concentration‐dependent MicroRNA release by chondrocytes, synoviocytes, and meniscus cells. Issue 5 (23rd November 2015) - Genemaras, Amaris A.; Ennis, Hayley; Kaplan, Lee; Huang, Chun‐Yuh
ABSTRACT: In knee osteoarthritis (OA), concentrations of interleukin (IL)‐1β and tumor necrosis factor (TNF)‐α increase in joint tissues and synovial fluid which incite a catabolic cascade and further the progression of OA. Several microRNAs (miRNA) have been associated with apoptosis (miR‐16), inflammation (miR‐22, miR‐146a), and matrix degradation (miR‐140, miR‐27b) in developed OA or its symptoms. In this study, the time‐ and concentration‐dependent nature of cellular and extracellular miRNAs in synoviocytes, meniscus cells, and chondrocytes as influenced by inflammatory cytokines was investigated. For time‐dependent studies, three cell types were stimulated with 10 ng/ml IL‐1β or 50 ng/ml TNF‐α for 8, 16, and 24 h. For concentration‐dependent studies, chondrocytes were stimulated with a higher level of IL‐1β (20 ng/ml) or TNF‐α (100 ng/ml) for 8 h. Cellular and extracellular expressions of miR‐22, miR‐16, miR‐146a, miR‐27b, and miR‐140 were analyzed by RT‐PCR. Time‐dependent cellular miRNA expressions were similar across the three cell types with miR‐146a significantly up‐regulated and miR‐27b significantly down‐regulated at all time points. However, chondrocytes exhibited a unique extracellular miRNA profile with an increased release rate of miR‐27b at 24 h. Our findings support further research into the characterization of miRNAs in synovial fluid for the development of early detection strategies of OA or cartilage injury. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:779–790, 2016.